The comprehension of relative clauses by monolingual and bilingual speakers of Portuguese and English - Maia, Marcus; Maia, Juliana (Revista Leitura, 2019)
The present study investigates the comprehension of Portuguese and English ambiguous relative sentences by native and L2 learners of both English and Portuguese. Our preliminary results in an offline questionnaire seem to indicate that Universal Grammar principles may not be directly accessible to adult L2 learners as it is to child L1 learners because L1 processing strategies may be influencing the comprehension of L2 input. DOI: 10.28998/0103-6858.2001n28-29p29-41